The Effect of Cognitive Behavioral Therapy on Depression and Quality of Life in Chronic Kidney Disease Patients: A Quasi-Experimental Study - Nazaruddin Nazaruddin; Cece Indriani; Icha Novitasari; Akbar Ramadhani (Journal of Health and Nutrition Research, 2026)
Chronic Kidney Disease (CKD) imposes substantial physical and psychological burdens, with depression significantly exacerbating the decline in patients' health-related quality of life (QOL). This study aimed to assess the efficacy of Cognitive Behavioral Therapy (CBT) in alleviating depressive symptoms and enhancing the QOL of CKD patients. Methods: A quasi-experimental study was conducted with 70 CKD patients experiencing depressive symptoms (BDI > 14), who were divided into intervention (n=35) and control (n=35) groups. The intervention group underwent an eight-week CBT program consisting of structured weekly sessions (30–60 minutes each), while the control group received routine medical care only. Depression and QOL were evaluated pre- and post-intervention using the Beck Depression Inventory (BDI) and the WHOQOL instrument, respectively. Analysis using the Mann-Whitney test showed a statistically significant improvement in the intervention group compared with the control group (p = 0.000). Following the intervention, 48.6% of participants in the CBT group transitioned to a "no depression" state, and 60.0% reported a "good" QOL, whereas the control group remained largely unchanged with high rates of severe depression. The integration of structured CBT into clinical nursing care provides a robust, holistic approach to improving the psychological and physical well-being of CKD patients. These results underscore the importance of incorporating routine mental health screening and evidence-based psychological interventions into standard renal care protocols.